Improved quinoa growth, physiological response, and seed nutritional quality in three soils having different stresses by the application of acidified biochar and compost - Ramzani, Pia Muhammad Adnan (Plant physiology and biochemistry : PPB, 2017)
Copyright © 2017. Published by Elsevier Masson SAS.